The Involvement of Firms in Helping Fight the Pandemic of COVID-19 : Evidence from Indonesia - Ahmad Abbas; Mohamad Ilham; Neks Triani; Ainun Arizah; Wa Ode Rayyani (Politeknik Negeri Bengkalis, 2020)
The purpose of this study is to demonstrate the magnitude of firms socially involved in helping fight the pandemic of COVID-19. This study highlights 680 go public firms in Indonesia. The content analysis is used to find the information of firms’ social involvement. The result point of this study demonstrates that from 680 go public firms listed during the pandemic, there are only seven and one-half percent of companies involved in combating the coronavirus outbreak. Firms provide the donation including funds, free internet services, nutrition products, masks, and medical supplies. They have recognized their social involvement as the form of corporate social responsibility